INTEGRITAS LAPORAN KEUANGAN DILIHAT DARI INTELLECTUAL CAPITAL DAN LEVERAGE - Budiman K; Muhammad Rivandi (JURNAL PUNDI, 2023)
The information in the submitted financial reports must be relevant and reliable so that the decisions taken by investors are not biased, and that the financial statements have integrity. The aim of this research is to examine the effect of Intellectual Capital and leverage on the Integrity of Financial Statements in transportation sector companies. The population used in this study are transportation sector companies listed on the Indonesia Stock Exchange in 2019 – 2021. The research sample consisted of 11 companies selected using the Purposive Sampling technique and 3 years of observation. The research method uses the Panel Regression method. The results show that Intellectual Capital has no effect on the Integrity of Financial Statements and leverage has a positive and significant effect on the Integrity of Financial StatementsKeywords - Financial Statement Integrity, Intellectual Capital, leverage.